A comparative analysis of alternative splicing in A. Thaliana and C. Reinhardtii - Labadorf, Adam, author; Ben-Hur, Asa, advisor; Rajopadhye, Sanjay Vishnu, committee member; Reddy, Anireddy S. N., committee member (Colorado State University. Libraries, 2010)
The extent of and mechanisms causing alternative splicing in plants are not currently well understood. A recent study in the model organism Arabidopsis thaliana estimates that approximately 42% of intron-containing genes are alternatively spliced and it is speculated that this number may be much higher. Results from our previous studies showed that the single celled alga Chlamydomonas reinhardtii also exhibits alternative splicing characteristic of plants. In this work we present the results of a comprehensive alternative splicing analysis using the largest Expressed Sequence Tag (EST) datasets available for both of these organisms, describe an analysis pipeline tailored to these large datasets, and conduct a cross-organism comparative analysis of aspects related to alternative splicing.